Factor VII activating protease - Kanse, S. M.; Etscheid, M. (Hämostaseologie, 2011)
Factor VII activating protease (FSAP) is a circulating serine protease with high homology to fibrinolytic enzymes. A role in the regulation of coagulation and fibrinolysis is suspected based on in vitro studies demonstrating activation of FVII or pro-urokinase plasminogen activator (uPA). However, considering the paucity of any studies in animal models or any correlative studies in humans the role of FSAP in haemostasis remains unclear. In relation to vascular remodeling processes or inflammation it has been convincingly shown that FSAP interacts with growth factors as well as protease activated receptors (PAR). Against this sparse background there are a plethora of studies which have investigated the linkage of single nucleotide polymorphisms (SNP) in the FSAP gene (HABP2) to various diseases. The G534E SNP of FSAP is associated with a low proteolytic activity due to an amino acid exchange in the protease domain. This and other SNPs have been linked to carotid stenosis, stroke as well as thrombosis in the elderly and plaque calcification. These SNP analyses indicate an important role for FSAP in the regulation of the haemostasis system as well as fibroproliferative inflammatory processes.
Keywords: FSAP; growth factor; HABP2; inflammation; remodelling; SNP; thrombosis